(untitled) (Journal of Mental Health & Well-being, 2025)
From Morocco to New York, experts are sounding the alarm: Internet addiction is no longer just a bad habit it’s a life disrupting disorder. Internet Addiction Disorder (IAD) rewires the brain, fuels anxiety, and damages relationships, making it one of the most urgent yet underestimated crises of the digital age. As Internet access expands in Morocco, Internet addiction is emerging as a significant issue, particularly among the younger generation. This study outlines a method to assess the level of Internet addiction among Moroccan high school students. The primary aim is to analyze students’ Internet usage and examine the correlation between excessive use and addictive tendencies. Longitudinal Structured Observation and the Internet Addiction Test (IAT) were employed to evaluate the severity of addictive behavior. The findings suggest that Moroccan youth are indeed vulnerable to Internet addiction.